Deserving poor in public sanitation: Tracing the policymaking processes of who gets what, when, how, and why in Delhi. (October 2022) - Bhan, Tanushree
This study investigates why sanitation outcomes vary across urban poor communities in Delhi, India. Unequal access to quality sanitation has serious implications for the health, dignity, and economic well-being of the poor and public health in general due to risks of environmental contamination. For this multiple-case study, a sample of 7 communities is drawn from slums, public housing, and homeless shelters. The database comprises of direct observations of sanitation outcomes in these communities, interviews with 67 key policy informants, official documents of relevant government agencies, newspaper articles, and court filings. The qualitative dataset is analyzed using process-tracing to uncover policy decisions across communities. Findings show that inequitable sanitation outcomes are manufactured by biases that blame the poor for service deficits and make the provision of entitled benefits contingent on political mobilization of exhibiting "good citizenship." This has serious implications for democratic accountability between the government and the very citizens that are most in need of public services to meet their sanitation needs.